Overkill: sex and violence in contemporary Russian popular culture - Borenstein, Eliot (Culture and society after Socialism, 2008)
About that : sex and its metaphors -- Stripping the nation bare : pornography as politics -- Pimping the motherland : Russia bought and sold -- To be continued : death and the art of serial storytelling -- Women who run with the wolves -- Men of action : heroic melodrama and the passion of Mad Dog -- Overkill : bespredel and gratuitous violence -- Conclusion : someone like Putin